Hypoglycemia induces vascular endothelial dysfunction in subjects with normal glucose tolerance - Tanaka, Kenichi; Okada, Yosuke; Torimoto, Keiichi; Nishio, Kosuke; Narisawa, Manabu; Tanaka, Yoshiya (Scientific reports, 2022)
This prospective study determined the effects of hypoglycemic stimulation on vascular endothelial function in non-diabetic patients using reactive hyperemia peripheral arterial tonometry (RH-PAT). The study included non-diabetic patients who were hospitalized for an insulin tolerance test (ITT) for the diagnosis of hypoadrenocorticism or hypopituitarism. Vascular endothelial function was assessed using the reactive hyperemia index (RHI) measured by the RH-PAT. We also measured the levels of anterior pituitary hormone, adrenaline, noradrenaline, and dopamine at the time of hypoglycemia. The primary endpoint was a change in the RHI at 120 min after insulin administration. The study included 27 patients. ITT was associated with significant increases in systolic blood pressure, pulse rate, and the blood levels of adrenocorticotropic hormone, cortisol, growth hormone, adrenaline, noradrenaline, and dopamine. RHI significantly decreased after ITT from 2.24 ± 0.51 to 1.71 ± 0.42. A significant inverse correlation was observed between the change in RHI and change in adrenaline (r = − 0.670, p = 0.012). We concluded that hypoglycemic stimulation altered vascular endothelial function, as measured by RH-PAT, even in patients free of glucose intolerance. The observed deterioration in vascular endothelial function correlated with increases in catecholamine levels during hypoglycemia. Trial registration: UMIN000033244.